Analysis of the Influence of Instagram Social Media on Brand Loyalty Through Brand Trust and Brand Equity on Bilka Supermarket Product Salesin Surabaya - Badriyyah, Shania; Mubarokah; Setyadi, Taufik (AJARCDE (Asian Journal of Applied Research for Community Development and Empowerment), 2025)
trust, and equity, and examine the management strategies Bilka uses to maintain product purchases via social media. A quantitative approach with questionnaires was used, involving active Instagram users. Descriptive statistical analysis and SEMPLS were applied. The results show a diverse consumer age range, with most respondents aged 18-35. Instagram significantly influences brand loyalty, trust, and equity, which positively impacts sales. The management strategies include continuous promotions, active consumer interaction, and attractive offers. In conclusion, Instagram is an effective tool for strengthening consumer relationships and boosting sales when the right strategies are applied. Contribution to Sustainable Development Goals (SDGs):SDG 8: Decent Work and Economic GrowthSDG 9: Industry, Innovation, and InfrastructureSDG 12: Responsible Consumption and ProductionSDG 17: Partnerships for the Goals